Bewegung versus Avantgarde? Mythologie der linken Debatten über die Russische Revolution 1917 - Kasakow, Ewgeniy (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
In the leftist debates, one of the most widespread notions is that in 1917 workers and peasants were about to build their own model of socialism, and only the Bolshevik bureaucracy hindered them. In the struggle between the councils and the party, the former are regarded as representatives of a left alternative to the authoritarian Bolsheviks. Only rarely are such assumptions examined by means of archival documents and new studies based on them.